Existence of a solution of the quasi-variational inequality with semicontinuous operator - Jovanov, Đurica S. (Yugoslav Journal of Operations Research, 2006)
The paper considers quasi-variational inequalities with point to set operator. The existence of a solution, in the case when the operator of the quasi-variational inequality is semi-continuous and the feasible set is convex and compact, is proved.